UJI KARAKTERISTIK SIFAT FISIK DAN PEMBAKARAN MINYAK JELANTAH SEBAGAI BAHAN BAKAR KOMPOR YANG MENGGUNAKAN SUMBU KOMPOR - Fery Adi; Edward Saleh; R. Mursidi Mursidi (Jurnal Teknik Pertanian Sriwijaya, 2012)
The research objective was to study physical characteristic of discarded cooking oil combustion as the energy sources for wick stove. This research used Group Randomized Design consisting of two factors with three levels and three replications. The first factor is the filtration treatment of used cooking oil (A), and the second factor is the treatment of used cooking oil temperature (B). The parameters observed were firing rate, rate capillarity, viscosity, density, flash point, porosity and surface tension. The results showed the temperature and filtering of each treatment have significant effect on the rate of combustion, the rate of capillarity. Interaction of temperature and filtration respectively has significant effect on the rate of combustion and spur capillarity. The results showed that combined treatment temperature of 700C with a screening filter paper (A3B3) is the best treatment with the burning rate of 0.0189 mL / s, while combined treatment temperature of 700C with no filtering (A3B1) is the best treatment at the rate of capillarity 0.01173 mL / s.Keywords : cooking oil, rate capillarity, viscosity, density